Intellectual origins of the Frankfurt School - Muhammad, Rania; Azeez, Mohammed (Al-Adab Journal, 2025)
The Frankfurt School is one of the most prominent contemporary Western philosophical schools that has spread. Because of its pioneers who influenced the school’s philosophical production throughout its three generations. The importance of researching the intellectual origins of this school lies in the fact that it constituted an important turning point in the path of contemporary European thought, as it had a great and effective impact in formulating a critical theory that deals with sociology, philosophy, politics, and culture as overlapping and intertwined dimensions in the process of forming and studying social theories and cognitive and civilizational horizons. Which accompanied the developments and transformations witnessed by European society in the fields of economics and politics. The fame that the Frankfurt School gained, and the wide spread of its ideas and their influence on Western intellectual and philosophical production, prompts the following question: What are the intellectual origins from which this school derived its fame and spread? The research assumes that there is a relationship of influence between the philosophies that were prevalent at the beginning of the emergence of the Frankfurt School, and its three generations are only a reflection of what those who assumed the leadership of this school believed in them and the ideas that dominated or influenced the trends that were subject to research, scrutiny and criticism. The most prominent findings reached by the two researchers are: The pioneers of the Frankfurt School from the first generation were influenced by the concepts of psychology and the results of its research, and employed them in their various studies. We find in the writings of these pioneers indications that the texts of the joint authorship of Horkheimer and Adorno (The Dialectic of Enlightenment) demonstrate the presence of the Freudian spectrum. In the thought of the pioneers of the Frankfurt Critical School.